The application of blended learning with rADI model to improve argumentation skills and concept mastery - Dea Yuliyanti; Widi Purwianingsih; P. Peristiwati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Post-pandemic policies encourage teachers and students to carry out learning in offline, where they used to go online before. One learning strategy that can be applied in this condition is blended learning, which combines the advantages of offline and online learning. In improving the quality of learning outcomes and developing students' 21st-century skills, especially argumentation skills, blended learning strategies can be combined with inquiry-based learning models, one of which is the revised Argument-Driven Inquiry (rADI). This study aims to obtain an analysis of data related to the application of blended learning with rADI model in improving students' argumentation skills and concept mastery in Monera materials, especially regarding Bacteria. The research method used in this study was pre-experimental with a one-group pretest-posttest design. This research was conducted on students of class X MIPA at a high school in Bandung which consisted of 26 students. The data were obtained from the pre-test and post-test results of argumentation skills and concept mastery, and questionnaires on students' responses to learning. The results showed an increase in students’ argumentation skills with an N-Gain score of 0.81 and students’ concept mastery with an N-Gain score of 0.78 after applying blended learning with rADI model. The increase in argumentation skills and concept mastery was significant with N-Gain scores included in the high category. In addition, students' response data showed a good response to the application of blended learning with rADI model.